A Cross-Sectional Study on Central Sensitization and Autonomic Changes in Fibromyalgia - Hazra, Sandipan; Venkataraman, Srikumar; Handa, Gita; Yadav, S. L.; Wadhwa, Sanjay; Singh, U.; Kochhar, K. P.; Deepak, K. K.; Sarkar, Kaushik (Frontiers in Neuroscience, 2020)
Fibromyalgia is a multi-symptomatic disorder characterized by generalized pain. The pathophysiology of fibromyalgia is supposedly an interplay between central nervous system hyper-responsiveness, autonomic dysfunction and peripheral pain. In this cross-sectional study, the objective was to assess central sensitization and autonomic activity in patients with fibromyalgia and compare with control. Fifty adults diagnosed with fibromyalgia by modified American College of Rheumatology 2010 criteria and an equal number of age and sex-matched controls participated in the study in an urban tertiary care hospital. Central sensitization was assessed by history and by evidence of increased pre-frontal cortical activity as measured by cortical oxygenation using functional near infrared spectroscopy. Autonomic activity was assessed by heart rate variability, electrodermal activity and deep breathing test in three physiological states: rest, sympathetic stress (cold pressor test) and deep breathing. Mann-Whitney U test, paired t-test, Wilcoxon and Frideman’s test with Bonferroni priori were used to analyze the data. Cortical activity was significantly higher in the fibromyalgia group than control. There was no significant difference in autonomic activity between the fibromyalgia and control group. In the fibromyalgia group, variable degree of sympathetic hyperactivity and normal parasympathetic activity were observed. Central sensitization may be playing a primary role in the pathophysiology of generalized pain in fibromyalgia.